Analisis Kualitas Hidup P2K Narkotika pada Penerima Layanan Rehabilitasi Rawat Jalan BNN Tahun 2022 - Mayasari, Febriana Kusuma Dian; Erza, Essi Septia; Nurhotimah; Saprina, Indri Maulia (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2024)
Drug abuse has become a global phenomenon and poses a serious threat to society at local, national, regional, and international levels. The National Narcotics Agency (BNN), as the leading sector in the Prevention and Eradication of Drug Abuse and Illicit Trafficking (P4GN), has a policy direction in the field of rehabilitation aimed at improving rehabilitation facilities to enhance the quality of life of drug abusers, addicts, and/or victims of drug abuse (P2K). This study was conducted using mixed methods: a qualitative approach through in-depth interviews with clients and significant others, and a quantitative approach by identifying and analyzing each variable in the WHOQoL-BREF in its impact on the quality of life of drug abuse victims. The study's findings indicate that the WHOQoL condition of outpatient clients is at a good level, with recovery and empowerment in both public and domestic spaces. This condition is not only influenced by the clients' and families' commitment and motivation but also by their experiences during rehabilitation services.